PERENCANAAN PEMBANGUNAN SMART CITY: Studi Tentang Program Internet Keren di Kota Blitar - Waskita Putra, Kuncahya (Jurnal Administrasi Publik, 2023)
Smart City Development Planning (Study of Internet Keren Programs in Blitar City). The city of Blitar has implemented a smart city since 2019, but only officially implemented it in 2023 through Blitar Mayor Regulation Number 23 of 2023 concerning the Implementation of a Smart City. These include the provision of internet or WiFi in all RTs to the availability of connected optical cables in all regional apparatus organizations. In general, Blitar City has been good at preparing hardware and software. The city of Blitar really needs smart city solutions to improve better governance based on information technology. Apart from that, there is a need to develop human resources because state civil servants or government employees have not utilized technology well with many challenges in implementing a smart city in Blitar City. The Blitar City Government carries out technical guidance to plan and follow up on the implementation of smart city in Blitar City. Smart city development indicators in Blitar City include smart government, Smart Environment, Smart Branding, Smart Economy, smart society, Smart Living. The community has made good use of internet keren programs in the context of smart city development in Blitar City, but in terms of community participation, especially in providing input regarding smart city development in Blitar City, it is still not optimal. The aim of this research is to explain and analyze smart city development planning regarding the cool internet program in Blitar City, the actors involved as well as the supporters and obstacles. The research method used is qualitative which aims to describe and analyze smart city development planning